Membangun Keterlibatan dan Pemberdayaan Masyarakat, Komunitas Lingkungan untuk Kemajuan Desa - Hanifah, Hanifah; Perdana, Buyung Cahya; Arvita, Rizki; Hariono, Jefri (PUTRA JAWA PUBLISHER, 2024)
Building community engagement and empowerment, particularly in the context of environmental communities, plays a crucial role in achieving sustainable village development. This article outlines the concepts and strategies that can be used to strengthen community engagement and empowerment in the context of rural development. By using a participatory and needs-based approach, environmental communities can actively participate in planning, implementing, and evaluating various development programs and projects. Through cross-sector collaboration and the utilization of local resources, environmental communities can enhance their capacity and self-reliance in addressing environmental and social challenges. Thus, this article provides practical guidance for stakeholders to accelerate the village development process through inclusive and resilient sustainable development.